(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Obstetric health care was always an important problem in countries where human resources are decisive. The research carried out was the basis of innovation and training for obstetrical human resources, meeting people’s needs. Objectives: Describe the current situation and needs of obstetricians working at provincial and district hospitals in representative ecological regions in Vietnam. Methods: A cross-sectional descriptive study in 7 provinces/cities, including 27 hospitals. Results: The situation and demand for human resources specialized in obstetrics and gynecology were mostly in the Red River Delta (>40%), mainly at the provincial level (>54%). By 2025, the Central Coast and South Central region will have the highest demand for human resources for obstetricians (from 15.5% in 2020 to 30.3%). The Obstetrician-Gynecologist’s human resources are still lacking in number, causing overcrowding. The need for specialized training support in technical knowledge and skills, procedures and surgery is closely related to the local situation. Conclusion: The situation and demand for obstetrical human resources in 2020-2025 are concentrated in the Red River Delta at provincial hospitals. The number of obstetrician human resources has not been able to fully and promptly respond to patients. However, the quality of staff is guaranteed, and the capacity is enough to meet the service.